Emerging Market versus Western Expatriates in Japan during the Covid-19 Pandemic - Bebenroth, Ralf; Nahar, Yasmin Nur (Organizations and Markets in Emerging Economies, 2022)
In this paper, the term “EMex” is coined to refer to emerging market expatriates who had to adjust to working and living in Japan during the Covid-19 pandemic. The Social Identity Theory is applied together with the Grounded Theory to develop a more nuanced picture of how EMex coped with the adjustment process. We found that EMex were confronted with various challenges, some of which were somewhat similar, while others were quite different compared to those experienced by the Western expatriates. All the interviewees in this study spent most of their assignment duration in Japan at their home office. Occasionally, when EMex were allowed to go to their office, they were assigned to special projects with international teams, and so they did not have any contact with non-English speaking local (Japanese) managers. Like Western expatriates, they also missed in-person meetings with their workmates at the office; in spite of their IT literacy, they also faced challenges conducting online meetings from their home office. EMex were not given housing allowance, and this added to the difficulty in adjusting to living in Japan compared to Western expatriates. Moreover, their motivations and perspectives of the future differed from those of Western managers, who had a more secure future with their company. Also EMex faced out-group categorization issues by host-country nationals (HCNs) even if some of them planned to extend their stay in Japan after their assignment ended.
Keywords: Emerging Market expatriates; Bangladesh; German; Japan; Social Identity theory; Grounded theory